Climate impacts and crop responses in US corn and wheat production region - Zhao, Haidong (Kansas State University, 2024)
The global impact of climate change on food production poses a critical challenge in sustaining the world’s population. Projections of climate demonstrate changes of temperature and precipitation in the future, challenging the security of global food including the US Great Plains and Midwest, which are wheat and maize breadbaskets, respectively. While wheat yields have increased in the US Great Plains over the past several decades, the persisting threat of climate change has led to stagnation and even collapse in some states. Conversely, maize yields in the US Midwest have exhibited a consistent upward trend since the 1930s. However, understanding the driving forces behind the changes in crop yields remains an open empirical question. This dissertation is structured to address three primary objectives: 1) identifying the impact of compound climate extreme on wheat yields; 2) determining the contributors of maize yield trends; and 3) quantifying the adaptation of maize hybrids to climate change. The study employs an array of datasets encompassing long-term surface climate, regional satellite observations, crop varieties/hybrids, crop phenology, yields, and field management practices (e.g., planting densities). Both statistical- and crop progress- based models (Hybrid-Maize model) were the main approaches used in this study. Firstly, statistical modeling of winter wheat yield variations indicated that compound hot-dry-windy (HDW) events are main drivers resulting in yield losses in the past four decades (1982-2020), accounting for a 4% yield reduction per 10 hours of HDW during the growth period from heading to maturity. Furthermore, climate change has significantly increased HDW events, which are associated with yield reduction rates of up to 0.09 t ha⁻¹ per decade. Additionally, HDW variations are atmospheric-bridged with the Pacific Decadal Oscillation. We quantify the “yield shock”, which is spatially distributed, with the losses in severely HDW-affected areas, the same areas affected by the Dust Bowl of the 1930s. Secondly, analysis of drivers of maize yield trends indicated that surface solar radiation (SSR) shows only a weak contribution to maize yield gains because SSR did not change significantly in the US Midwest in the past four decades. Conversely, non-environmental factors (e.g., genetic and management improvement) are the main drivers of yield increases, supported using the Hybrid-Maize model which is a process-based model. Finally, we analyze an extensive dataset from maize hybrid field performance tests conducted in five maize-producing states in the US Corn Belt between 2000 and 2020. We found a consistent increase in maize yields under varying environmental stress levels, with an average of 0.15 t ha⁻¹ yr⁻¹. We also found that breeding efforts have enhanced the resilience of maize yields to VPD, with an average increase of 0.06 t ha⁻¹ kPa⁻¹ yr⁻¹. However, even when cultivating current hybrids under high-emission shared socio-economic pathways (SSP5-8.5) climate scenarios, additional increases in VPD caused a 4% reduction in maize yield relative to averaged historical yield losses. This dissertation explored the impact of climate change on winter wheat and maize yield variability and trends, highlighting the adaptation of winter wheat crop varieties and corn hybrids in the US breadbasket. These insights offer valuable considerations for farmers and agronomists, emphasizing the need for proactive measures to adapt to the challenges posed by climate change in the future.
Keywords: Climate impacts; Maize yields; Winter wheat yields; Hot-dry-windy events; Surface solar radiation; Vapor pressure deficit